Endocuff-assisted colonoscopy is associated with a lower adenoma miss rate: a multicenter randomized tandem study - Triantafyllou, Konstantinos; Polymeros, Dimitrios; Apostolopoulos, Periklis; Lopes Brandao, Catarina; Gkolfakis, Paraskevas; Repici, Alessandro; Papanikolaou, Ioannis S.; Dinis-Ribeiro, Mario; Alexandrakis, George; Hassan, Cesare (Endoscopy, 2017)
Background and study aims The Endocuff (ARC Medical Design, Leeds, UK) is a device that, when mounted on the tip of an endoscope, may assist with inspection of a greater surface of the colonic mucosa by pulling backwards, flattening, and stretching the colonic folds as the endoscope is gradually withdrawn. We aimed to compare the adenoma miss rates of Endocuff-assisted colonoscopy with those of conventional colonoscopy. Patients and methods The included patients underwent same-day, back-to-back, (Endocuff-assisted colonoscopy as the index procedure followed by conventional colonoscopy or vice versa, randomly assigned 1:1) colonoscopies, performed by six endoscopists with documented adenoma detection rates > 35 %, in four tertiary endoscopy facilities. Results We randomized 200 patients (mean age 61.2 years [standard deviation 9.8]; 86.5 % colorectal cancer screening surveillance cases). Overall, there were seven incomplete examinations using Endocuff and one with conventional colonoscopy (P = 0.03). Times for endoscope insertion (5.0 minutes [0.8 – 21.0] vs. 5.0 minutes [1.0 – 16.0]; P = 0.49) and withdrawal (6.0 minutes [3.2 – 29.0] vs. 6.0 minutes [3.1 – 17.0]; P = 0.06) were similar for Endocuff-assisted and conventional colonoscopy. We detected one cancer and 195 adenomas; 84 in the proximal colon. Endocuff-assisted colonoscopy showed significantly lower overall and proximal colon adenoma miss rates compared with conventional colonoscopy (14.7 % [8.0 % – 21.0 %] vs. 38.4 % [28.1 % – 48.6 %] and 10.4 % [1.8 % – 19.1 %] vs. 38.9 % [23.0 % – 54.8 %], respectively). No difference between the two arms was shown regarding advanced adenoma miss rates, either overall or in the proximal colon. There were no serious adverse events related to the procedures. Conclusions In comparison with conventional colonoscopy, Endocuff-assisted colonoscopy has a significantly lower adenoma miss rate when performed by high-detector endoscopists. However, the incomplete colonoscopy rate with Endocuff is higher.ClinicalTrials.gov Identifier: NCT02340065.